Pengaruh Kesehatan, Keselamatan, Faktor Motivasi, dan Komitmen Organisasional terhadap Kepuasan Kerja Karyawan - Shertin Ayu Fitria; Rojuaniah Rojuaniah (Pusat Riset dan Inovasi Nasional, 2025)
Employee occupational health is of particular concern to all companies, as healthy employees are considered the pillars of organizational success. The purpose of occupational health is to increase job satisfaction and employee participation so that when measuring employee job satisfaction, occupational health is used as a major factor. This study explores the influence of occupational health, safety, and organizational commitment on employee job satisfaction at PT JNE, West Jakarta using quantitative methods. It was found that motivational factors significantly influence job satisfaction, highlighting the importance of motivating employees. Although occupational health and safety did not show a significant direct influence, their implementation remains essential to overall job satisfaction. In addition, increasing organizational commitment through employee engagement and developing corporate culture is also necessary. This research underscores the importance of effective internal communication and data-driven human resource strategies, calling on PT JNE to continuously evaluate and adapt their strategies in a dynamic work environment.